Pension reforms and couples' labour supply decisions - Hamed M. Moghadam; Patrick A. Puhani; Joanna Tyrowicz (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
To determine how wives' and husbands' retirement options affect their spouses' (and their own) labour supply decisions, we exploit (early) retirement cutoffs by way of a regression discontinuity design. Several German pension reforms since the early 1990s have gradually raised women's retirement age from 60 to 65, but also increased ages for several early retirement pathways affecting both sexes. We use German Socio-Economic Panel data for a sample of couples aged 50 to 69 whose retirement eligibility occurred (i) prior to the reforms, (ii) during the transition years, and (iii) after the major set of reforms. We find that, prior to the reforms, when several retirement options were available to both husbands and wives, both react almost symmetrically to their spouse reaching an early retirement age, that is both husband and wife decrease their labour supply by about 5 percentage points when the spouse reaches age 60). This speaks in favour of leisure complementarities. However, after the set of reforms, when retiring early was much more difficult, we find no more significant labour supply reaction to the spouse reaching a retirement age, whereas reaching one's own retirement age still triggers a significant reaction in labour supply. Our results may explain some of the diverse findings in the literature on asymmetric reactions between husbands and wives to their spouse reaching a retirement age: such reactions may in large parts depend on how flexibly workers are able to retire.
Keywords: J22; J26; 330; retirement coordination; labour market participation; household decisions; regression discontinuity design